The influence of climate on water chemistry states and dynamics in rivers across Australia. Issue 12 (14th December 2021) - Lintern, Anna; Liu, Shuci; Minaudo, Camille; Dupas, Rémi; Guo, Danlu; Zhang, Kefeng; Bende‐Michl, Ulrike; Duvert, Clément
Abstract: For effective water quality management and policy development, spatial variability in the mean concentrations and dynamics of riverine water quality needs to be understood. Using water chemistry (calcium, electrical conductivity, nitrate‐nitrite, soluble reactive phosphorus, total nitrogen, total phosphorus and total suspended solids) data for up to 578 locations across the Australian continent, we assessed the impact of climate zones (arid, Mediterranean, temperate, subtropical, tropical) on (i) inter‐annual mean concentration and (ii) water chemistry dynamics as represented by constituent export regimes (ratio of the coefficients of variation of concentration and discharge) and export patterns (slope of the concentration‐discharge relationship). We found that inter‐annual mean concentrations vary significantly by climate zones and that spatial variability in water chemistry generally exceeds temporal variability. However, export regimes and patterns are generally consistent across climate zones. This suggests that intrinsic properties of individual constituents rather than catchment properties determine export regimes and patterns. The spatially consistent water chemistry dynamics highlights the potential to predict riverine water quality across the Australian continent, which can support national riverine water quality management and policy development. Abstract : Continental scale analysis of water chemistry across five climate zones in Australia Significantly different mean concentrations across climate zones No clear variation in water chemistry dynamics across climate zones Spatial variability in water chemistry generally exceeds temporal variability